A High-Resolution MRI Study of the Relationship Between Plaque Enhancement and Ischemic Stroke Events in Patients With Intracranial Atherosclerotic Stenosis - Wang, ErLing; Shao, Sai; Li, Shan; Yan, Peng; Xiang, YuanYuan; Wang, Xiang; Li, JiFeng; Wang, Guangbin; Sun, QinJian; Du, YiFeng (Frontiers in Neurology, 2019)
Purpose: To investigate the relationships among the degree of intracranial atherosclerotic stenosis (ICAS), plaque enhancement (PE), and ischemic stroke events (ISEs) using 3.0T high-resolution magnetic resonance imaging (HR-MRI). Materials and Methods: Fifty-two ICAS patients who underwent HR-MRI were retrospectively analysed. The patients were divided into two groups according to the results of whole-brain digital subtraction angiography (DSA): the mild-moderate stenosis group (group MID) and the severe stenosis group (group SEV). According to the onset time of the ISEs, the plaques were divided into the acute/sub-acute phase culprit plaque group (group ACU, within one month), the chronic-phase culprit plaque group (group CHR, more than one month), and the nonculprit plaque group (group NON). Two neuroradiologists independently measured the signal intensity of PE and pituitary enhancement in the HR-MRI and calculated the radio of the two indices. According to the ratio, the patients were divided into 3 groups: the marked enhancement group (group MA), the mild enhancement group (group ME), and the no enhancement plaque group (group NO). The relationships among the degree of ICAS, the degree of PE and ISEs were analysed. Results: Seventy-two ICAS plaques were identified in 52 patients. The multiple independent samples Kruskal-Wallis H test showed that the differences among group ACU, CHR, and NON were significant in the degree of PE (P=0.002). Group CHR and group NON were combined as the non-acute phase group (group non-ACU). Group NO and group ME were combined as the non-marked enhancement group (gruop non-MA). The comparison between group ACU and group non-ACU showed significant differences in the degree of both ICAS (P=0.014) and PE (P=0.006) according to the univariate logistic regression. The multivariate logistic regression model was used to analyse the impact of the degree of ICAS and PE on ISEs, and the results showed that severe stenosis (P=0.036) and marked PE (P=0.013) were independent risk factors for acute ISEs, respectively. Conclusion: Severe intracranial arterial stenosis and marked plaque enhancement are independent risk factors for acute ischemic stroke events, respectively. The study provides new ideas for further exploring the pathogenesis of stroke caused by intracranial atherosclerotic stenosis.